Distribution and Antibiotic Resistance of Escherichia coli on Public Transport Routes in Makassar City: Implications for Resistance Surveillance - M. Ahlil Vadel Tila; Sulfikar; Nur Alisah; Maryono; Zuhrah Adminira Ruslan (Sakura Digital Nusantara, 2026)
The resistance of bacteria to antibiotics is a significant challenge in combating infections. Public transportation can be a hotspot for the spread of antibiotic-resistant bacteria. We surveyed the presence of Escherichia coli (E. coli) resistant to antibiotics on public transport cars, locally named Pete-Pete, serving four routes in Makassar, Indonesia. Swab samples were collected from door handles, walls, and seats, of 12 public transport vehicles (3 per route across 4 routes). Antibiotic resistance was evaluated using the Kirby-Bauer Disk Diffusion method and the EUCAST standard for resistance determination. We found widespread distribution of antibiotic-resistant E. coli at all locations, with variation in resistance patterns between locations. High resistance percentages were found in E. coli samples from two routes bordering other districts. Multi-resistant strains of E. coli to four types of antibiotics were found in samples from one route bordering the Gowa District. Our research indicates the potential for identifying distribution patterns and detecting levels of antibiotic resistance in pathogens through sampling public transportation.